Multi-layer composite pike racket and preparation process thereof

By adopting multi-layer composite material design, using honeycomb structures of different materials and three-dimensional five-way weaving technology, the problems of easy wear and aging of traditional rackets are solved, and the high wear resistance, strength and stability of rackets are achieved, and the service life is extended. And improves the user experience.

CN119386445APending Publication Date: 2025-02-07DONGGUAN XINSHUO COMPOSITE MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411842812.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Due to the limitations of a single material, traditional pickle rackets are prone to wear and aging, have a short service life and are large in weight, which affects the flexibility and reaction speed of athletes and cannot meet the needs of most people.

Method used

Designed with multi-layer composite materials, including internal composite layers and outer layers, the internal composite layers consist of honeycomb structures of different materials, such as aramid honeycomb structure and polymethacryimide foam honeycomb structure, through three-dimensional five-way weaving technology Carbon fibers and aramid fibers are tightly combined to form composite fibers with high strength and wear resistance.

Benefits of technology

It significantly improves the wear resistance, mechanical strength and structural stability of the racket, extends the service life, enhances the athlete's batting experience and feel, meets the needs of most people, and improves the fun of sports.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of rackets, and particularly relates to a multi-layer composite Pick racket and a preparation process thereof.The multi-layer composite Pick racket comprises a racket plate and a racket handle, and the racket plate comprises an inner composite layer and an outer layer; the inner composite layer at least comprises a first layer and a second layer; the first layer and the second layer are made of different materials; the first layer and the second layer are both made of any one of aramid fiber, polypropylene, aluminum alloy and polymethacrylimide foam. Through combination of different materials, the strength, the wear resistance and the structural stability of the Pick racket are improved, meanwhile, the requirements of most people can be met through multi-layer compounding, and the sports interestingness is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rackets, and in particular relates to a multi-layer composite pickle ball racket and a preparation process thereof. Background Art

[0002] In the field of pickleball, the performance of the racket is crucial to the performance of the players. Traditional pickleball rackets are mostly made of a single material, such as wood, metal or some synthetic materials. Although these materials have certain advantages in some aspects, rackets made of a single material are prone to wear and aging after long-term use, and are easily deformed or damaged, and have a short service life; rackets made of traditional materials are often heavy, which affects the flexibility and reaction speed of athletes; and a single material can only reflect one performance and feel, which reduces the user experience of sports enthusiasts, lacks fun, and cannot meet the needs of most people.

[0003] In view of the above technical problems, the present invention proposes a multi-layer composite pickle ball racket and a preparation process thereof to overcome the deficiencies in the prior art, improve the wear resistance, mechanical strength and structural stability of the pickle ball racket, and enhance the user experience. Summary of the invention

[0004] The purpose of the present invention is to provide a multi-layer composite pickle ball racket and a preparation process thereof, which can improve the strength, wear resistance and structural stability of the pickle ball racket through the combination of different materials. At the same time, the multi-layer composite can also meet the needs of most people and improve the fun of sports.

[0005] A multi-layer composite pickle ball racket comprises a racket board and a racket handle, wherein the racket board comprises an inner composite layer and an outer layer; the inner composite layer comprises at least a first layer and a second layer; the first layer and the second layer are both honeycomb structures.

[0006] The first layer and the second layer are made of different materials; the first layer and the second layer are made of any one of aramid, polypropylene, aluminum alloy, and polymethacrylimide foam, forming aramid honeycomb structure, polypropylene honeycomb structure, aluminum alloy honeycomb structure, and polymethacrylimide foam honeycomb structure respectively.

[0007] Preferably, the honeycomb side length of the aramid honeycomb structure is 1.8-2 mm; and the honeycomb diameter of the polymethacrylimide foam honeycomb structure is 6-8 mm.

[0008] The aramid honeycomb is prepared from raw materials including aramid fiber, carbon fiber, epoxy resin and curing agent.

[0009] Preferably, the aramid fiber has a fineness of 500-1000 dtex and an elongation at break of 3%-3.5%.

[0010] In some preferred embodiments, the aramid fiber is purchased from DuPont Kevlar aramid fiber, K29AP, from the United States.

[0011] Preferably, the carbon fiber has a diameter of 6.5-7.5 μm and a tensile modulus of ≥4900 MPa.

[0012] In some preferred embodiments, the carbon fiber is purchased from Toray of Japan, T700SC-12K.

[0013] Preferably, the epoxy resin has a viscosity of 6000-10000 mPa·s at 25° C. and an epoxy value of 0.45-0.50 eq / 100 g.

[0014] Preferably, the curing agent has a viscosity of 50-100 mPa·s at 25°C and a density of 0.98-1.02 g / cm 3 .

[0015] In some preferred embodiments, the epoxy resin and curing agent are purchased from Changshu Jiafa Chemical Co., Ltd., JC-05A and JC-05B.

[0016] The preparation method of the aramid honeycomb comprises the following steps: washing and drying aramid fiber and carbon fiber, using aramid fiber as braiding yarn and carbon fiber as axial yarn, and obtaining composite fiber through three-dimensional five-way braiding; putting the composite fiber into an aramid honeycomb mold, adding a mixed liquid of epoxy resin and curing agent to immerse the composite fiber, evacuating the mold, maintaining the temperature at 85-95°C for 1.5-2.5h, and then heating to 120-130°C for 3-5h to obtain the aramid honeycomb.

[0017] Preferably, the number of the aramid fibers is 20-30.

[0018] Preferably, the number of the carbon fibers is 10-20.

[0019] Preferably, the mass ratio of the epoxy resin to the curing agent is 100:(75-77).

[0020] Preferably, the density of the aramid honeycomb is 70-90 kg / m 3 , thickness is 5-9mm.

[0021] The inventors found that the use of a composite fiber obtained by mixing specific carbon fiber and aramid fiber and using it to prepare an aramid honeycomb can improve the hardness, strength and wear resistance of this side of the pickle ball racket. This may be because the carbon fiber and aramid fiber complement each other synergistically. The carbon fiber provides the racket's skeleton support with its high strength and high modulus, ensuring the racket's stability and accuracy when hitting the ball, while the aramid fiber enhances the racket's impact resistance and service life with its good wear resistance and corrosion resistance. In addition, aramid fiber also has a certain elasticity, which can absorb and disperse the impact force during the hitting process, improving the comfort and feel of the racket. During the preparation process, the carbon fiber and aramid fiber are closely combined together through a three-dimensional five-way weaving technology to form a composite fiber with a honeycomb structure. This structure not only improves the bonding force between the fibers, but also enables the racket to distribute stress more evenly when subjected to force, thereby further enhancing the strength and durability of the racket. At the same time, after adding epoxy resin and curing agent, the composite fiber is closely combined with the honeycomb mold through a specific curing process to form an aramid honeycomb with high density and excellent performance. Therefore, the aramid honeycomb obtained by using the composite fiber of carbon fiber and aramid fiber can significantly improve the performance and service life of the pickleball racket when preparing the racket, providing athletes with a better hitting experience and feel. However, a racket made of only one material cannot meet the needs of most people.

[0022] The polymethacrylimide foam honeycomb is prepared from raw materials, by weight, including 95-105 parts of main monomer, 5-10 parts of regulating monomer, 1-3 parts of crosslinking agent, 0.2-0.3 parts of initiator, 3-5 parts of foaming agent and 5-10 parts of nanoparticles.

[0023] Preferably, the main monomers include methacrylic acid and (meth)acrylonitrile; further preferably, methacrylic acid and acrylonitrile.

[0024] Preferably, the mass ratio of methacrylic acid to acrylonitrile is 1:(1.2-1.5).

[0025] Preferably, the regulating monomers include methyl methacrylate, ethyl methacrylate, allyl methacrylate, tert-butyl methacrylate, n-butyl methacrylate, tridecyl methacrylate, and methyl styrene; further preferably, allyl methacrylate, tridecyl methacrylate, and methyl styrene.

[0026] Preferably, the mass ratio of allyl methacrylate, tridecyl methacrylate and methyl styrene is 1:(8-12):(18-22); more preferably, it is 1:5:10.

[0027] Preferably, the cross-linking agent includes (meth)acrylamide, N,N-methylenebisacrylamide, ethylene glycol dimethacrylate, and bismaleimide; further preferably, acrylamide and N,N-methylenebisacrylamide.

[0028] Preferably, the mass ratio of acrylamide to N,N-methylenebisacrylamide is (4-6):1; more preferably, it is 5:1.

[0029] Preferably, the initiator includes one or more of azobisisobutyronitrile and azobisisoheptylnitrile; further preferably, it is azobisisobutyronitrile.

[0030] Preferably, the foaming agent includes formamide, isopropanol, and tert-butanol; further preferably, it is formamide.

[0031] The inventors found that the chemical stability and durability of the polymethacrylimide foam honeycomb can be improved by using a specific monomer combined with a crosslinking agent to prepare the polymethacrylimide foam honeycomb. This may be because the main monomers methacrylic acid and acrylonitrile ensure that the foam honeycomb has excellent mechanical properties and chemical stability, methacrylic acid provides good polymerization reaction activity, and the addition of acrylonitrile significantly enhances the heat resistance and wear resistance of the foam, so that the racket can still maintain excellent performance during long-term use. The monomers allyl methacrylate, tridecyl methacrylate and methyl styrene are adjusted to work synergistically, and the foam is made more uniform and delicate by adjusting the polymerization reaction rate and segment length. At the same time, the toughness and elasticity of the foam are improved, so that the racket can better absorb and disperse the impact force when hitting the ball, provide better feel and control, and further optimize the structure and performance of the foam honeycomb. The crosslinking agent is selected from acrylamide and N, N-methylenebisacrylamide, and each polymer segment is tightly connected together by forming a crosslinked network, thereby improving the compressive strength and tear resistance of the foam, so that the racket can maintain structural integrity when subjected to external force impact, and is not easy to deform or break. At the same time, the hardness of the foam honeycomb is relatively soft, and using it in the second layer of the pickleball racket can meet the needs of most people. However, its friction resistance is poor, which affects the life of the racket.

[0032] Preferably, the nanoparticles include one or more of modified nano-silicon dioxide, organic montmorillonite, kaolin, and talc; further preferably, they are modified nano-silicon dioxide.

[0033] The preparation method of the modified nano silicon dioxide comprises the following steps:

[0034] B1. Take a silane coupling agent and hydrolyze it in a 75-85wt% ethanol aqueous solution, add nano-silicon dioxide, stir at 55-65°C for 2-4h, filter and dry to obtain substance 1;

[0035] B2, graphene oxide is dispersed evenly in an organic solution, isocyanate is added, stirred at 80-100°C for 30-40h, filtered and dried to obtain substance 2;

[0036] B3. Mix substance 1 and substance 2 to obtain a mixture, disperse the mixture in an organic solvent, stir at 80-100°C for 20-30h, filter and dry to obtain the mixture.

[0037] Preferably, the silane coupling agent includes 3-(methacryloyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0038] Preferably, the mass ratio of the 3-(methacryloyloxy)propyltrimethoxysilane to γ-aminopropyltriethoxysilane is 1:(4-6); more preferably, it is 1:5.

[0039] Preferably, the volume ratio of the silane coupling agent to the 75-85wt% ethanol aqueous solution is 1:30-50; more preferably, it is 1:40.

[0040] Preferably, the nano-silicon dioxide includes a first nano-silicon dioxide, a second nano-silicon dioxide, and a third nano-silicon dioxide.

[0041] Preferably, the mass ratio of the first nano-silicon dioxide, the second nano-silicon dioxide, and the third nano-silicon dioxide is (2-4):(1-3):1; more preferably, it is 3:2:1.

[0042] Preferably, the average particle size of the first nano-silicon dioxide is 15 nm and the specific surface area is 250 m 2 / g.

[0043] Preferably, the average particle size of the second nano-silicon dioxide is 30 nm and the specific surface area is 200 m 2 / g.

[0044] Preferably, the third nano-silicon dioxide has an average particle size of 60 nm and a specific surface area of ​​150-200 m 2 / g.

[0045] In some preferred embodiments, the nano-silicon dioxide is purchased from Beijing Dekedaojin Technology Co., Ltd.

[0046] Preferably, the added amount of the silane coupling agent is 2% to 8% of the mass of the nano-silicon dioxide.

[0047] Preferably, the isocyanate is p-phenylene diisocyanate, and the added amount is 80-100 times the mass of graphene oxide.

[0048] Preferably, the graphene oxide includes a first graphene oxide and a second graphene oxide.

[0049] Preferably, the weight ratio of the first graphene oxide to the second graphene oxide is (1-3):1; further preferably, it is 2:1.

[0050] Preferably, the first graphene oxide has an average thickness of 0.5-1.2 nm, a diameter of 4-7 μm, and one layer.

[0051] Preferably, the second graphene oxide has an average thickness of 1-3 nm, a diameter of 4-7 μm, and 2-5 layers.

[0052] In some preferred embodiments, the graphene oxide is purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0053] Preferably, the organic solvent is N,N-dimethylformamide.

[0054] Preferably, in step B2, the mass ratio of graphene oxide to organic solution is 1:15-25; further preferably, it is 1:20.

[0055] Preferably, the mass ratio of the nano-silicon dioxide to graphene oxide is (8-12):1.

[0056] Preferably, in step B3, the mass ratio of the mixture to the organic solution is 1:15-25; more preferably, it is 1:20.

[0057] The inventors found that by selecting three specific nano-silicon dioxide as one of the raw materials of nanoparticles, and modifying it with graphene oxide after surface treatment with a silane coupling agent, it is possible to improve the mechanical properties of the foam honeycomb while improving its wear resistance and adjusting the hardness. First, the nano-silicon dioxide with different particle sizes and specific surface areas not only increases the specific surface area and porosity of the material through the construction of a multi-level structure, but also enables the material to better disperse and withstand stress when subjected to external forces, thereby improving the wear resistance and fatigue resistance of the material. The nano-silicon dioxide with a smaller particle size can fill the pores and form a tight stack, reducing the defects and cracks inside the material, and further enhancing the hardness and strength of the material. However, long-term and frequent use will cause the hardness of the foam honeycomb to be too low, unable to bear the greater shear stress of the friction pair, resulting in an increase in the wear rate, and the nano-particle size of silicon dioxide is prone to agglomeration, affecting the performance of the foam honeycomb. The inventors creatively found that by introducing a specific graphene oxide with lubricating properties, it can work synergistically with nano-silicon dioxide, so that the racket can better resist deformation and wear when subjected to external forces, and improve wear resistance. The first graphene oxide and the second graphene oxide have similar diameters and little difference in thickness. The compounding of the two realizes complementarity in the number of layers, which not only retains the high activity of the single-layer graphene oxide, but also improves the mechanical properties of the product. On the other hand, the graphene oxides of similar size are intertwined and stacked to form a stable three-dimensional network structure, which can improve the structural stability of the foam honeycomb finally prepared. Silane coupling agent, as a bridge connecting nano-silicon dioxide and graphene oxide and other components, not only significantly improves the interface bonding force and overall strength of the material through chemical bonding, but also enhances the interaction force inside the foam honeycomb, so that each component can give full play to its performance advantages and jointly improve the wear resistance and hardness of the foam honeycomb. It can also improve the dispersion and uniformity of nanomaterials, reduce the occurrence of agglomeration, and further improve the comprehensive performance of the foam honeycomb.

[0058] The preparation method of the polymethacrylimide foam honeycomb comprises the following steps: mixing raw materials, stirring at a speed of 200-400 r / min at 55-65° C. for 1-3 hours, pouring the raw materials into a polymethacrylimide foam honeycomb mold, standing at 45-50° C. for 48-72 hours, heating to 70-80° C. and maintaining for 3-5 hours, heating to 160-180° C. for foaming for 8-10 hours, and finally heat treating at 140-160° C. for 6-8 hours to obtain the product.

[0059] Preferably, the density of the polymethacrylimide foam honeycomb is 50-60 kg / m 3 , thickness is 5-9mm.

[0060] The material of the outer layer includes any one of a rubber layer and a fiber layer. The specific preparation method can refer to patent CN118217608B.

[0061] The method for preparing the multi-layer composite pickleball racket comprises the following steps:

[0062] S1, bonding the first layer and the second layer to obtain an inner composite layer;

[0063] S2. Wrap the outer layer on the outer surface of the inner composite layer, put it into a mold for hot pressing to obtain a racket board, and then install the racket handle to obtain the racket board.

[0064] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0065] 1. The present invention provides a multi-layer composite pickle ball racket, which improves the strength, wear resistance and structural stability of the pickle ball racket through the combination of different materials. At the same time, the multi-layer composite can also meet the needs of most people and improve the fun of sports.

[0066] 2. The present invention uses a composite fiber obtained by mixing specific carbon fiber and aramid fiber, and uses the composite fiber to prepare an aramid honeycomb, which can improve the hardness, strength and wear resistance of the side of the pickle ball racket.

[0067] 3. The present invention prepares the polymethacrylimide foam honeycomb by selecting a specific monomer combined with a cross-linking agent, which can improve the chemical stability and durability of the polymethacrylimide foam honeycomb.

[0068] 4. The present invention selects three specific nano-silicon dioxide as one of the raw materials of nanoparticles, and uses silane coupling agent to treat the surface and then uses graphene oxide to modify it, so as to improve the mechanical properties of the foam honeycomb, improve its wear resistance, and adjust the hardness. DETAILED DESCRIPTION

[0069] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0070] The raw materials described in the present invention are all commercially available, and are specifically as follows:

[0071] The aramid fiber has a fineness of 500-1000 dtex and an elongation at break of 3%-3.5%, and is purchased from DuPont Kevlar aramid fiber, K29AP, from the United States.

[0072] The carbon fiber has a diameter of 6.5-7.5 μm and a tensile modulus of ≥4900 MPa, and is purchased from Toray, Japan, T700SC-12K.

[0073] The viscosity of epoxy resin at 25°C is 6000-10000mPa·s, and the epoxy value is 0.45-0.50eq / 100g; the viscosity of curing agent at 25°C is 50-100mPa·s, and the density is 0.98-1.02g / cm 3 ; Both were purchased from Changshu Jiafa Chemical Co., Ltd., JC-05A and JC-05B.

[0074] The average particle size of the first nano-silicon dioxide is 15nm and the specific surface area is 250m 2 / g; the average particle size of the second nano-silicon dioxide is 30nm and the specific surface area is 200m 2 / g; the average particle size of the third nano-silicon dioxide is 60nm, and the specific surface area is 150~200m 2 / g; all purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0075] The average thickness of the first graphene oxide is 0.5~1.2nm, the diameter is 4~7μm, and the number of layers is 1; the average thickness of the second graphene oxide is 1~3nm, the diameter is 4~7μm, and the number of layers is 2~5; both were purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0076] Example 1

[0077] The present embodiment provides a multi-layer composite pickle ball racket, including a racket board and a racket handle, wherein the racket board includes an inner composite layer and an outer layer; the inner composite layer includes a first layer and a second layer; the first layer and the second layer are both honeycomb structures.

[0078] The first layer and the second layer are made of different materials; the first layer is made of aramid; the first layer is made of polymethacrylimide foam, forming an aramid honeycomb structure and a polymethacrylimide foam honeycomb structure respectively.

[0079] The honeycomb side length of the aramid honeycomb structure is 1.8 mm; the honeycomb diameter of the polymethacrylimide foam honeycomb structure is 6 mm.

[0080] The aramid honeycomb is prepared from aramid fiber, carbon fiber, epoxy resin and curing agent.

[0081] The preparation method of the aramid honeycomb comprises the following steps: washing and drying aramid fiber and carbon fiber, using aramid fiber as braiding yarn and carbon fiber as axial yarn, and obtaining composite fiber through three-dimensional five-way braiding; placing the composite fiber into an aramid honeycomb mold, adding a mixed liquid of epoxy resin and curing agent to immerse the composite fiber, evacuating the mold, maintaining the temperature at 90° C. for 2 hours, and then heating to 125° C. for 4 hours to obtain the aramid honeycomb.

[0082] The number of the aramid fibers is 25.

[0083] The number of the carbon fibers is 15.

[0084] The mass ratio of the epoxy resin to the curing agent is 4:3.

[0085] The density of the aramid honeycomb is 80kg / m 3 , thickness is 7mm.

[0086] The polymethacrylimide foam honeycomb is prepared from raw materials, by weight, including 100 parts of main monomer, 8 parts of regulating monomer, 2 parts of crosslinking agent, 0.25 parts of initiator, 4 parts of foaming agent and 8 parts of nanoparticles.

[0087] The main monomers are methacrylic acid and acrylonitrile, with a mass ratio of 10:13.

[0088] The regulating monomers are allyl methacrylate, tridecyl methacrylate and methyl styrene, and the mass ratio is 1:5:10.

[0089] The cross-linking agent is acrylamide and N,N-methylenebisacrylamide, and the mass ratio is 5:1.

[0090] The initiator is azobisisobutyronitrile.

[0091] The foaming agent is formamide.

[0092] The nanoparticles are modified nano silicon dioxide.

[0093] The preparation method of the modified nano silicon dioxide comprises the following steps:

[0094] B1, hydrolyze the silane coupling agent in an 80wt% ethanol aqueous solution, add nano-silica, stir at 60°C for 3h, filter and dry to obtain substance 1;

[0095] B2, dispersing graphene oxide evenly in an organic solution, adding isocyanate, stirring at 90°C for 35h, filtering and drying to obtain substance 2;

[0096] B3. Mix substance 1 and substance 2 to obtain a mixture, disperse the mixture in an organic solution, stir at 90° C. for 25 h, filter and dry to obtain the product.

[0097] The silane coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane, and the mass ratio is 1:5.

[0098] The volume ratio of the silane coupling agent to the 80wt% ethanol aqueous solution is 1:40.

[0099] The nano silicon dioxide includes first nano silicon dioxide, second nano silicon dioxide and third nano silicon dioxide, and the mass ratio is 3:2:1.

[0100] The added amount of the silane coupling agent is 5% of the mass of the nano-silicon dioxide.

[0101] The isocyanate is p-phenylene diisocyanate, and the added amount is 90 times the mass of graphene oxide.

[0102] The graphene oxide includes a first graphene oxide and a second graphene oxide, and the weight ratio of the first graphene oxide and the second graphene oxide is 2:1.

[0103] The organic solvent is N,N-dimethylformamide.

[0104] In the step B2, the mass ratio of graphene oxide to the organic solution (the organic solution described in step B2) is 1:20.

[0105] The mass ratio of the nano silicon dioxide to graphene oxide is 10:1.

[0106] In the step B3, the mass ratio of the mixture to the organic solution (the organic solution described in step B3) is 1:20.

[0107] The preparation method of the polymethacrylimide foam honeycomb comprises the following steps: mixing the raw materials, stirring at 60°C at a speed of 300 r / min for 2 hours, pouring the raw materials into a polymethacrylimide foam honeycomb mold, standing at 48°C for 55 hours, heating to 75°C and maintaining for 4 hours, heating to 170°C for foaming for 9 hours, and finally heat treating at 150°C for 7 hours to obtain the product.

[0108] The density of the polymethacrylimide foam honeycomb is 55kg / m 3 , thickness is 8mm.

[0109] The specific preparation method of the outer layer refers to Example 1 of patent CN 118217608B.

[0110] The preparation method of the multi-layer composite pickleball racket comprises the following steps:

[0111] S1, bonding the first layer and the second layer to obtain an inner composite layer;

[0112] S2. Wrap the outer layer on the outer surface of the inner composite layer, put it into a mold for hot pressing to obtain a racket board, and then install the racket handle to obtain the racket board.

[0113] Example 2

[0114] The difference between this embodiment and embodiment 1 is that the honeycomb side length of the aramid honeycomb structure is 2 mm; the honeycomb diameter of the polymethacrylimide foam honeycomb structure is 8 mm.

[0115] Comparative Example 1

[0116] The difference between this comparative example and Example 1 is that the raw materials for preparing the aramid honeycomb are aramid fiber, epoxy resin and curing agent.

[0117] Comparative Example 2

[0118] The difference between this comparative example and Example 1 is that the regulating monomer is only allyl methacrylate.

[0119] Comparative Example 3

[0120] The difference between this comparative example and Example 1 is that the cross-linking agent is only acrylamide.

[0121] Comparative Example 4

[0122] The difference between this comparative example and Example 1 is that the nanoparticles are nano-silicon dioxide.

[0123] Comparative Example 5

[0124] The difference between this comparative example and Example 1 is that the nano-silicon dioxide is only the first nano-silicon dioxide.

[0125] Comparative Example 6

[0126] The difference between this comparative example and Example 1 is that the preparation method of the modified nano-silica comprises the following steps: hydrolyzing a silane coupling agent in an ethanol aqueous solution with a concentration of 80 wt %, adding nano-silica, stirring at 60° C. for 3 h, filtering and drying to obtain the modified nano-silica.

[0127] Comparative Example 7

[0128] The difference between this comparative example and Example 1 is that the first layer and the second layer are not honeycomb structures. The preparation method of the first layer comprises the following steps: wash and dry the aramid fiber and the carbon fiber, use the aramid fiber as the weaving yarn and the carbon fiber as the axial yarn, and obtain the composite fiber through three-dimensional five-way weaving; put the composite fiber into a pickle ball racket mold, add the epoxy resin and the curing agent mixture and immerse the composite fiber, evacuate the mold, keep it at 90°C for 2 hours, heat it to 125°C and keep it for 4 hours, and obtain the product. The preparation method of the second layer comprises the following steps: mix the raw materials, stir them at 300r / min at 60°C for 2 hours, pour them into the pickle ball racket mold, let them stand at 48°C for 55 hours, heat them to 75°C and keep them for 4 hours, then heat them to 170°C for foaming for 9 hours, and finally heat treat them at 150°C for 7 hours, and obtain the product. The density of the aramid honeycomb is 160kg / m 3 The thickness is 7mm. The density of the polymethacrylimide foam honeycomb is 120kg / m 3 , thickness is 8mm.

[0129] Performance Testing

[0130] The hardness test was conducted according to GB / T 2411-2008; the tensile strength test of the aramid honeycomb layer was conducted according to GB 10573-89; the tensile strength test of the polymethacrylimide foam honeycomb layer was conducted according to GB 9641-88; the friction and wear test of the polymethacrylimide foam honeycomb layer was conducted according to GB / T3960-2016. 10 volunteers were selected for each sample, and they played with the prepared pickleball racket. After half an hour, the feel of the racket was evaluated, with a score of 1-10. The higher the score, the better the feel. The average value was taken. The results are shown in Table 1.

[0131]

[0132] According to statistics, the multi-layer composite pickle ball racket prepared by Examples 1 to 2 of the present invention has specific mechanical properties in both layers, good wear resistance, low density, and good hand feel, which can meet the needs of most people, so that the prepared pickle ball racket can be hit on both sides and has different hand feels, thereby improving the fun of sports. In Comparative Example 1, the aramid honeycomb layer does not add carbon fiber, Comparative Example 2 does not add the adjusting monomers tridecyl methacrylate and methyl styrene, Comparative Example 3 does not add the cross-linking agent N,N-methylenebisacrylamide, Comparative Example 4 does not modify the nano-silicon dioxide, Comparative Example 5 only has one kind of nano-silicon dioxide, Comparative Example 6 does not graft graphene oxide, and Comparative Example 7 is not prepared into a honeycomb structure. The mechanical properties, hardness, friction coefficient, and hand feel of the prepared pickle ball racket are all poor. Therefore, the multi-layer composite pickle ball racket prepared by the raw materials and methods described in this application has certain strength, wear resistance, and structural stability, and at the same time has a good hand feel. The double-sided composite meets the needs of most people and improves the fun of sports.

[0133] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A multi-layer composite pickleball racket, characterized in that: The invention comprises a clapper and a handle, wherein the clapper comprises an inner composite layer and an outer layer; the inner composite layer comprises at least a first layer and a second layer; the first layer and the second layer are both honeycomb structures; the materials of the first layer and the second layer are different; the materials of the first layer and the second layer are both any one of aramid, polypropylene, aluminum alloy, and polymethacrylimide foam, forming an aramid honeycomb structure, a polypropylene honeycomb structure, an aluminum alloy honeycomb structure, and a polymethacrylimide foam honeycomb structure respectively; the raw materials for preparing the aramid honeycomb include aramid fiber, carbon fiber, epoxy resin, and curing agent; the fineness of the aramid fiber is 500-1000dtex, and the elongation at break is 3%-3.5%; the diameter of the carbon fiber is 6.5-7.5μm, and the tensile modulus is ≥4900MPa.

2. The multi-layer composite pickleball racket according to claim 1, characterized in that: The honeycomb side length of the aramid honeycomb structure is 1.8-2 mm; the honeycomb diameter of the polymethacrylimide foam honeycomb structure is 6-8 mm.

3. The multi-layer composite pickleball racket according to claim 2, characterized in that: The polymethacrylimide foam honeycomb is prepared from raw materials, by weight, including 95-105 parts of main monomer, 5-10 parts of regulating monomer, 1-3 parts of crosslinking agent, 0.2-0.3 parts of initiator, 3-5 parts of foaming agent and 5-10 parts of nanoparticles.

4. The multi-layer composite pickleball racket according to claim 3, characterized in that: In parts by weight, the main monomers include methacrylic acid and (meth)acrylonitrile.

5. The multi-layer composite pickleball racket according to claim 4, characterized in that: The regulating monomers include methyl methacrylate, ethyl methacrylate, allyl methacrylate, tert-butyl methacrylate, n-butyl methacrylate, tridecyl methacrylate, and methyl styrene.

6. The multi-layer composite pickleball racket according to claim 5, characterized in that: The nanoparticles include one or more of modified nano-silicon dioxide, organic montmorillonite, kaolin and talc.

7. The multi-layer composite pickleball racket according to claim 6, characterized in that: The preparation method of the modified nano silicon dioxide comprises the following steps: B1. Take a silane coupling agent and hydrolyze it in a 75-85wt% ethanol aqueous solution, add nano-silicon dioxide, stir at 55-65°C for 2-4h, filter and dry to obtain substance 1; B2, graphene oxide is dispersed evenly in an organic solution, isocyanate is added, stirred at 80-100°C for 30-40h, filtered and dried to obtain substance 2; B3. Mix substance 1 and substance 2 to obtain a mixture, disperse the mixture in an organic solvent, stir at 80-100°C for 20-30h, filter and dry to obtain the mixture.

8. The multi-layer composite pickleball racket according to claim 7, characterized in that: The silane coupling agent includes 3-(methacryloyloxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.

9. The multi-layer composite pickleball racket according to claim 8, characterized in that: The preparation method of the polymethacrylimide foam honeycomb comprises the following steps: mixing raw materials, stirring at a speed of 200-400 r / min at 55-65° C. for 1-3 hours, pouring the raw materials into a polymethacrylimide foam honeycomb mold, standing at 45-50° C. for 48-72 hours, heating to 70-80° C. and maintaining for 3-5 hours, heating to 160-180° C. for foaming for 8-10 hours, and finally heat treating at 140-160° C. for 6-8 hours to obtain the product.

10. A process for preparing the multi-layer composite pickle ball racket according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, bonding the first layer and the second layer to obtain an inner composite layer; S2. Wrap the outer layer on the outer surface of the inner composite layer, put it into a mold for hot pressing to obtain a racket board, and then install the racket handle to obtain the racket board.

Citation Information

Patent Citations

  • Lightweight pickleball paddle

    CA3038087A1

  • Multi-layer composite pickleball racket

    CN112870660A

  • Pick racket and preparation method thereof

    CN115155026A

  • Pick racket with integrated structure and preparation process thereof

    CN118217608A

  • Multi-layer composite pike racket

    CN220632943U

Cited By

  • Pick racket with TPU (thermoplastic polyurethane) film

    CN121177732A